The effect of aqueous extract of Iranian oak (Quercus brantii) on lipid profile and liver enzymes in beta-thalassemia patients: a randomized controlled trial, double-blind, placebo-controlled - Satehi, Mahdi Babamir; Karimi, Mahdi; Eskandari, Ataollah; Mahmoodi, Hamid (Frontiers in Nutrition, 2025)
Background and aimBeta-thalassemia major patients often require regular blood transfusions, leading to iron overload, oxidative stress, and disturbances in lipid metabolism. The common use of vitamins and iron chelators helps mitigate some of these effects, but lipid profile abnormalities persist. The oak fruit (Quercus brantii) is rich in antioxidant compounds, such as flavonoids and polyphenols, which may help address these issues. This study aimed to investigate the effects of the aqueous extract of Iranian oak on the lipid profile and liver enzymes in beta-thalassemia major patients.Materials and methodsThis randomized, double-blind, placebo-controlled clinical trial included 60 beta-thalassemia major patients (29 males, 31 females; age 10–60 years) who regularly received blood transfusions and deferoxamine. Participants were divided into two groups: the intervention group received Iranian oak extract capsules (300 mg/day), and the control group received placebo capsules for 3 months. Lipid profiles (cholesterol, triglycerides, HDL, LDL) and liver enzymes (ALT, AST) were measured before and after the intervention.ResultsThe control group exhibited a significant increase in triglyceride levels (from 167 to 184 mg/dL, p < 0.03), while no significant changes were observed in the intervention group. In contrast, total cholesterol significantly decreased in the oak extract group (from 125 to 112 mg/dL, p < 0.003). HDL levels decreased in both groups (p = 0.008 for the intervention group; p = 0.016 for the control group). No significant differences were found in LDL, ALT, or AST levels between the two groups.ConclusionThe aqueous extract of Iranian oak demonstrated potential lipid-modulating effects by preventing triglyceride increases and reducing cholesterol levels in beta-thalassemia major patients. These findings suggest that the antioxidant properties of the oak extract may help manage lipid abnormalities associated with iron overload, improving cardiovascular risk profiles in these patients. Further studies with larger sample sizes and extended follow-up are recommended to confirm these benefits.Clinical trial tegistrationhttp://www.irct.ir, identifier IRCT2015101411819N4.